Finding Points of Intersection: Learning through Feminist Non-Credit Learning Processes - Christine McKenzie (Adult Education Research Conference, 2011)
The praxis I develop in this paper comes from this empirical research and is also based on my experience as an adult educator in non-credit contexts over the past 15 years. Following a brief overview of my study, I discuss key findings, which relates to the tension between holistic and challenging practices as methods for bringing differently-located women learners together and the impact of educators’ awareness of their social locations on learning processes. This research revealed the centrality of educators’ identity in their practices and the limitations of intersectionality and interlocking identities frameworks in praxis.
Keywords: feminist non-formal learning; consciousness-raising; intersectionality; interlocking oppression; feminist standpoint